Characteristics of Biocellulose from Sago Liquid Waste with Different Ammonium Sulfate Concentration - Nur Arfa Yanti (International Journal of Ecophysiology, 2019)
This research aims to utilize sago liquid waste to produce biocellulose with different concentration of ammonium sulfate and to know characteristics of biocellulose. Production of biocellulose was done in sago liquid waste substrate with different concentration of ammonium sulfate, namely 0.5, 1, 1.5 and 2% (w/v) by using bacteria local strain Acetobacter xylinum LKN6. The observed parameters included thickness, yield, crude fiber and organoleptic.The analysis results showed that ammonium sulfate concentration given a different to the thickness, yield, crude fiber and organoleptic. The best characteristic of biocellulose obtained in the treatment of 1.5% ammonium sulfate concentration. The biocellulose from sago liquid waste potential as dietary fiber food.